USE OF VILLAGE FUND OUTSIDE THE VILLAGE FUND PRIORITY (CONSTRUCTION OF A VILLAGE HALL IN ADIPASIR VILLAGE, RAKIT DISTRICT BANJARNEGARA REGENCY) - Ilham Mu’alim; Agoes Djatmiko; Esti Ningrum (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2022)
To find out the legal provisions and consequences of the use of Village Funds Outside the Priority of Village Funds (Development of Village Halls in Adipasir Village, Rakit District, Banjarnegara Regency). To achieve this goal the researcher uses the Normative Juridical Approach method, Research Specification is the application of law in abstracto in cases in concreto (Clinical Legal Research). The method of presenting data is presented in the form of a description arranged systematically, logically, and rationally. Conclusions: - Regulatively the Use of Village Funds Outside Priority for the Development of Adipasir Village Hall, Rakit District, Banjarnegara Regency is in accordance with the provisions in the Banjarnegara Regent's Letter Number: 142.41/148/Setda/2016-R dated April 25, 2016 concerning Recommendations on the Use of Village Funds in Outside the Priority of the Use of Village Funds for Fiscal Year 2016. - The legal consequences of the use of Village Funds outside the Priority of Village Funds for the Development of the Adipasir Village Hall, Rakit District, Banjarnegara Regency, namely there are no legal consequences, due to the approval of the Banjarnegara Regent in accordance with Article 27 Paragraph (1) Regulation of the Minister of Finance Number : 247/PMK.07/2015 concerning Procedures for the Allocation, Distribution, Use, Monitoring and Evaluation of Village Funds.